Rituximab biosimilar and reference rituximab in patients with previously untreated advanced follicular lymphoma (ASSIST-FL): primary results from a confirmatory phase 3, double-blind, randomised, controlled study. Issue 8 (August 2017) - Jurczak, Wojciech; Moreira, Ilídia; Kanakasetty, Govind Babu; Munhoz, Eduardo; Echeveste, Maria Asunción; Giri, Pratyush; Castro, Nelson; Pereira, Juliana; Akria, Luiza; Alexeev, Sergey; Osmanov, Eugeniy; Zhu, Peijuan; et al.
Summary: Background: GP2013 is a rituximab biosimilar developed to stringent development guidelines, including non-clinical and preclinical investigations and clinical trials in rheumatoid arthritis and follicular lymphoma. We aimed to compare the efficacy, safety, tolerability, pharmacokinetics, and pharmacodynamics of GP2013 plus cyclophosphamide, vincristine, and prednisone (GP2013-CVP) with rituximab-CVP (R-CVP) in patients with follicular lymphoma. Methods: In this phase 3, multinational, double-blind, randomised, controlled trial, adults (aged 18 years or older) with previously untreated, advanced stage (Ann Arbor stage III or IV) follicular lymphoma of WHO histological grades 1, 2, or 3a were randomly assigned (1:1) using interactive response technology to eight cycles of GP2013-CVP or R-CVP (combination phase), followed by monotherapy maintenance in responders for a 2-year period. Randomisation was stratified by Follicular Lymphoma International Prognostic Index risk group and geographic region. The primary endpoint was comparability in overall response, with equivalence concluded if the entire 95% CI was within a margin of −12% to 12%. The primary endpoint was analysed using the per-protocol set, which included all patients who received at least one (partial or complete) dose of investigational treatment and who did not have any major protocol deviations. The trial is registered withClinicalTrials.gov, numberNCT01419665, and is ongoing. Findings: Between Dec 1, 2011, and Jan 15, 2015, 858 patients were screened for eligibility. 314 patients were randomly assigned to GP2013, of whom 312 were given GP2013, and 315 were assigned to reference rituximab. Median follow-up was 11·6 months (IQR 5·8–18·2) for the primary analysis. The primary endpoint, equivalence of overall response, was met (271 [87%] of 311 patients with GP2013 and 274 [88%] of 313 patients with reference rituximab achieved an overall response; difference −0·40% [95% CI −5·94 to 5·14]). Occurrence of adverse events and serious adverse events was similar between the treatment groups (289 [93%] of 312 patients in the GP2013-CVP group had an adverse event and 71 [23%] of 312 patients had a serious adverse event; 288 [91%] of 315 patients in the R-CVP group had an adverse event and 63 [20%] had a serious adverse event). The most common adverse event was neutropenia (80 [26%] of 312 patients in the GP2013-CVP group and 93 [30%] of 315 patients in the R-CVP group in the combination phase and 23 [10%] of 231 patients in the GP2013-CVP group and 13 [6%] of 231 patients in the R-CVP group in the maintenance phase). The most common grade 3 or 4 adverse event during the combination and maintenance phase was neutropenia (55 [18%] of 312 patients in the GP2013-CVP group and 65 [21%] of 315 patients in the R-CVP group in the combination phase and 17 [7%] of 231 patients in the GP2013-CVP group and nine [4%] of 231 patients in the R-CVP group in the maintenance phase). The occurrence of anti-drug antibodies was similar in the treatment groups (five [2%] of 268 patients in the GP2013-CVP; three [1%] in the R-CVP group). Interpretation: Our results show that GP2013 represents a viable rituximab biosimilar candidate for patients with previously untreated advanced follicular lymphoma. The introduction of biosimilars provides additional therapeutic options with potential to increase access to effective and life-saving biological therapies such as rituximab. Funding: Hexal.